MANAJEMEN HUMAS POLRES KAMPAR DALAM MENDUKUNG PENURUNAN ANGKA KRIMINALITAS KABUPATEN KAMPAR TAHUN 2017 - Nafia, Syifa; Rasyid, Anuar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The police of the Republic of Indonesia have a mission of ensuring the success of handling domestic security disturbances, this is welcomed by the reality that existed in 2017 within the scope of work of Kampar District, Kampar Police has carried out the mission with the decreasing number of criminals from previous years and the largest decline seen in the Kampar Polres working unit when compared with other districts. Seeing the decline in crime indicates an increase to the preemptive, preventive, and repressive system conducted by Kampar Police in 2017 therefore this study aims to see how the management of PR which consists of Planning, Organizing, Actuating and Controlling carried out by Kampar Police in an effort to achieve its success.This research uses descriptive analysis with qualitative method. Research subjects consisted of four informants selected by using purposive technique. data were collected by interview, documentation and observation. For checking the validity of data, the authors do the extension of participation and also triangulationThe result of the research shows that the planning is started from the Analysis and Evaluation (Anev) at the end of the year which become the evaluation on the implementation of duty in the previous year to be used as the reference and the innovation in the implementation of the task next year, then continued with Progiat forum to discuss the program to be done and then continued on the smaller planning forums on each functional unit called RenGiat (Activity Plan). Organizing is done by departmentalization as well as division of labor which is determined by the board and the head of institution. Actuating stage carried out in a structured and coordinated between the target, the media, and also the implementer. While the stage of supervision carried out regularly so as to support the effectiveness of the implementation of each activity that has been planned before and after because the evaluation results will be a reference materials planning againKeyword : Public Relations Management, Planning, Organizing, Actuating, Controlling